At the queen's summons ebook - Wiggs, Susan (Tudor Rose, 2009)
Feisty orphan Pippa de Lacey lives by wit and skill as a London street performer. But when her sharp tongue gets her into serious trouble, she throws herself upon the mercy of Irish chieftain Aidan O'Donoghue. Pippa provides a welcome diversion for Aidan as he awaits an audience with the queen, who holds his people's fate in her hands. Amused at first, he becomes obsessed with the audacious waif who claims his patronage. Rash and impetuous, their unlikely alliance reverberates with desire and the tantalizing promise of a life each has always wanted--but never dreamed of attaining.